Large enhancement of thermoelectric performance in MoS₂/h-BN heterostructure due to vacancy-induced band hybridization - Wu, Jing (2021)
Local impurity states arising from atomic vacancies in two-dimensional (2D) nanosheets are predicted to have a profound effect on charge transport due to resonant scattering and can be used to manipulate thermoelectric properties. However, the effects of these impurities are often masked by external fluctuations and turbostratic interfaces; therefore, it is challenging to probe the correlation between vacancy impurities and thermoelectric parameters experimentally. In this work, we demonstrate that n-type molybdenum disulfide (MoS₂) supported on hexagonal boron nitride (h-BN) substrate reveals a large anomalous positive Seebeck coefficient with strong band hybridization. The presence of vacancies on MoS₂ with a large conduction subband splitting of 50.0 ± 5.0 meV may contribute to Kondo insulator-like properties. Furthermore, by tuning the chemical potential, the thermoelectric power factor can be enhanced by up to two orders of magnitude to 50 mW m⁻¹ K⁻² Our work shows that defect engineering in 2D materials provides an effective strategy for controlling band structure and tuning thermoelectric transport.